Establishment and characterization of transformed goat primary cells by expression of simian virus 40 large T antigen for orf virus propagations - Yamada, Yumiko; Liao, Guan-Ru; Tseng, Ching-Yu; Tseng, Yeu-Yang; Hsu, Wei-Li (PloS one, 2019)
Due to the limited host range of orf virus (ORFV), primary cells derived from its natural hosts, such as goats and sheep, are recommended for isolation and propagation of wild type ORFV. This situation limits the option for the study of virus-host interaction during ORFV infection since primary cells only support a few numbers of passages. SV40 T antigen is a viral oncoprotein that can abrogate replicative senescence, leading to an extended life span of cells. In this study, the transformation of two goat primary cells, fibroblast (FB) and testis (GT) cells, were achieved by stably expressing SV40 T antigen using the lentiviral technique. The presence of the gene encoding SV40 T antigen was validated by polymerase chain reaction (PCR) and western blot analyses. As evidenced by immunofluorescent microscopy, the two types of cells expressing SV40 T antigen (namely, FBT and GTT) were purified to homogeneity. Moreover, faster growth kinetics and a lower serum dependency were noticed in FBT and GTT, as compared with their counterpart parental cells. FBT and GTT remain permissive and can form plaque of ORFV, despite with different profiles; generally speaking, with SV40 T expression, ORFV forms plaques with smaller size and distinct margin. Most importantly, the prolonged life span of goat FBT and GTT serves as an ideal cell culture resource for ORFV isolation from the field, studies of ORFV pathogenesis and efficient vaccine development.